Looking Pro-Environmental behaviors From Government Employees in Indonesia: The Role of Green Work Climate as a Mediating Variable - Aryati, Ana Sofia (Journal of Business and Management Review, 2025)
Research Aims: This study aims to analyse the effect of ethical leadership (EL) on pro-enviromental behaviour (PEB). In addition, this study also examines the mediating role of organisational commitment and green work climate (GWC) in determining this relationship. This research was conducted on permanent employees in Batu City Government Design/methodology/approach: The collected data were analysed using PLS analysis. EL positively and significantly influences PEB. In addition, organisational commitment plays a role in mediating the relationship between EL and PEB. Similarly, the analysis shows that GWC mediates the relationship between EL and PEB. This study is novel in that it analyses public service workers, whereas previous studies have focused on manufacturing companies or other institutions. Research Findings/Contribution: Leaders who have ethical values are likely to optimise employees to adopt PEB. Institutions should focus on maintaining organisational commitment and a GWC that supports sustainability so that it can be key in facilitating the influence of EL on PEB.